Catalytic conversion of agricultural waste biomass into valued chemical using bifunctional heterogeneous catalyst: A sustainable approach - Fouzia Perveen; Muhammad Farooq; Abdul Naeem; Muhammad Humayun; Tooba Saeed; Ihtisham Wali Khan; Ghazala Abid (Catalysis Communications, 2022)
This work reports synthesis of an efficient MoO3/ZnCo2O4@CeO2, bifunctional heterogeneous catalyst for profitable conversion of corncob biomass into Levulinic acid. The physiochemical properties of the catalyst were studied by TG-DTA, BET, XRD, FESEM/SEM, EDX-Mapping and TPD to correlate them with the catalytic activity. The results exposed that the synthesized catalyst showed improved catalytic performance, providing Levulinic acid yield of 70.1% under 8 wt% catalyst loading at 200 °C temperature for 220 min. Moreover, the catalyst presented sufficient reusability and recycled for at least 3 times for Levulinic acid production from the biomass without any loss in the catalytic activity.